Exploring five common assumptions on Attention Deficit Hyperactivity Disorder. (17th April 2014) - Batstra, Laura; Nieweg, Edo H.; Hadders‐Algra, Mijna
Abstract The number of children diagnosed with attention deficit hyperactivity disorder (ADHD) and treated with medication is steadily increasing. The aim of this paper was to critically discuss five debatable assumptions on ADHD that may explain these trends to some extent. These are that ADHD (i) causes deviant behaviour, (ii) is a disease, (iii) is chronic and (iv) is best treated by medication and (v) that classification should precede treatment. Conclusion We argue that ADHD is not a disease, not the cause of deviant behaviour and in most cases not chronic. Treatment for attention and hyperactivity problems could start with psychosocial interventions and without a diagnostic label. A stepped diagnosis approach may reduce overdiagnosis without risking undertreatment.